Старините в прохода Траянови врата в пътеписите от XVI–XIX век - Ivan Valchev (Българско е-Списание за Археология)
The present article offers an analysis of the information presented in travel literature from the period between the 16th and 19th c., with a particular focus on the ruins located around Trajan’s Gate Pass. The descriptions of foreign travellers and the sketches, engravings and plans they left behind constitute the sole source of information about the ancient gate, which was destroyed in 1835, as well as about part of the fortifications connected to it, of which no remains have been preserved either. Although the earliest reference to the gate dates back to the 13th c., the first eyewitness account of the monument only dates from the first half of the 16th c. At that time, the appellation “Trajan’s Gate” had yet to be coined. The objective of this publication is to analyse the information provided about the antiquities themselves, as well as the attitudes of educated Western travellers who passed through the gate. The travelogues that have survived to the present day were written by individuals with a humanistic education and an interest in antiquity. Additionally, they were conversant with the works of ancient authors and the information they had left about the Balkans. Consequently, the ruins around Trajan’s Gate Pass are not overlooked. The article traces the evolution of the perception of the remains of the gate, its association with the name of the Roman emperor Trajan, its rise to fame and the expectations of travellers, who were subsequently disappointed. The stages in the reception of the ruins correspond to the development of interest in ancient monuments in general and those within the boundaries of the Ottoman Empire in particular.